Peranan Badan Pengawas Obat dan Makanan (BPOM) dalam Mengawasi Peredaran Obat Tradisional yang Mengandung Bahan Kimia Obat - Rahma Arsyi Amalia; Asti Sri Mulyanti (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research is motivated by the importance of health which is the capital for achieving prosperity in life. The widespread distribution of traditional medicines containing medicinal chemicals that are harmful to consumers means that this action is not in accordance with existing laws. The aim of this research is to find out the role of the POM in the distribution of traditional medicines that contain medicinal chemicals. The research method used is a qualitative method with a normative juridical research type, namely an approach taken by examining statutory regulations. With data sources in the form of literature studies and observations, and supported by direct interviews with related institutions. The research uses Responsibility Theory and Consumer Legal Protection Theory. The research results explain that the role of BPOM is to have the authority to grant or withdraw a production permit for a product based on the results of surveys, research and testing on a product that is produced and distributed in the community and must have a production permit and distribution permit from BPOM.